Association of vitamin D concentrations with gestational hypertension and pre-eclampsia: a Mendelian randomisation analysis. (November 2016) - Magnus, Maria C; Miliku, Kozeta; Lawlor, Debbie A; Felix, Janine F; Jaddoe, Vincent W V; Bonilla, Carolina; Fraser, Abigail
Abstract: Background: Vitamin D can suppress renin biosynthesis and vascular smooth cell proliferation, and modulates macrophage activity and cytokine production. Therefore, higher vitamin D concentrations might reduce the risk of pre-eclampsia. Unmeasured confounding is inherent in observational studies, and existing trials are small and heterogeneous in terms of dose and duration of vitamin D supplementation. We aimed to assess the causal associations of vitamin D with gestational hypertension and pre-eclampsia in two European cohorts. Methods: We conducted a Mendelian randomisation study to estimate the causal effect of 25-hydroxyvitamin D (25(OH)D) on gestational hypertension and pre-eclampsia. 7288 women participating in the Avon Longitudinal Study of Parents and Children (ALSPAC) and Generation R studies who had a singleton pregnancy and were normotensive before pregnancy were included. Single nucleotide polymorphisms (SNPs) in genes associated with vitamin D synthesis ( rs10741657 and rs12785878 ) and metabolism ( rs6013897 and rs2282679 ), associated with 25(OH)D in genome-wide association studies, were used as instruments, evaluated independently, and combined into synthesis, metabolism, and total genetic risk scores. The outcome was no previous hypertension, gestational hypertension, and pre-eclampsia. The observational analysis used multinomial logistic regression, the Mendelian randomisation analysis used instrumental variable probit regression, and a random-effects meta-analysis was used to combine results from all cohorts. Ethics approval was obtained from the ALSPAC Law and Ethics Committee and the Medical Ethical Committee of the Erasmus MC in Rotterdam. Findings: There was evidence of a threshold effect of 25(OH)D on pre-eclampsia (134 cases) in the observational analysis (associations across categories in women with 25(OH)D concentrations <25 nmol/L vs ≥75 nmol/L, adjusted relative risk 2·17, 95% CI 1·09–4·34). There was no association with gestational hypertension (744 cases). None of the four SNPs or the three genetic risk scores were associated with either pre-eclampsia or gestational hypertension. Finally, the Mendelian randomisation analysis did not support a causal association of 25(OH)D with gestational hypertension or pre-eclampsia (odds ratio 1·02 per nmol/L increase, 95% CI 1·00–1·03 and 0·98, 0·95–1·01) with total genetic risk score used as the instrument. Interpretation: We did not find evidence to support a causal role for vitamin D status in gestational hypertension or pre-eclampsia. Funding: MCM and AF are supported by a UK Medical Research Council fellowship (MR/M009351/1). VWVJ received a grant from the Netherlands Organization for Health Research and Development (NWO, ZonMw-VIDI 016.136.361) and a European Research Council Consolidator Grant (ERC-2014-CoG-648916). JFF has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement number 633595 (DynaHEALTH). KM has been financially supported through Erasmus Mundus Western Balkans (ERAWEB), a project funded by the European Commission.